FLOOD DISASTER ADAPTATION STRATEGY IN CERBON DISTRICT OF SOUTH KALIMANTAN, INDONESIA - Muzdalifah; Hanafie U. (Russian Journal of Agricultural and Socio-Economic Sciences, 2022)
Farming households have adaptation mechanisms in dealing with vulnerability due to the impact of climate variability, namely ecological, economic and social adaptation. Farming households that own land will have harvested reserves that can be used for food stocks and sold when they need funds for urgent needs. Based on the results of the AHP analysis, the priority order of adaptation mechanisms carried out by farmers in Cerbon District is ecological adaptation, economic adaptation, and social adaptation. Farmers mostly carry out ecological adaptations, including shifting the planting season, changing varieties, and adjusting plant types depending on the season. Economic adaptations carried out by farmers in the event of a crisis include selling previous harvests, withdrawing savings, selling livestock, and selling assets. The dominant social adaptation carried out by farmers is by utilizing social networks, such as borrowing money from relatives, neighbors, or rice field owners and using assistance from the government. Resilience action is a priority for rice farming households in Cerbon District by working in the on farm, off farm and nonfarm sectors.